Factors Affecting Financial Risk Tolerance on Young Investors in Indonesia - Farah Margaretha Leon; Angie Angie (Universitas Trisakti, 2019)
This study aims to analyze the influence of self-esteem, personality, and sensation seeking on financial risk tolerance. Data obtained directly through the distribution of questionnaires to 323 respondents i.e., young investors (aged 16 to 30 years) in Indonesia. The research design used in this research is hypothesis testing. The analytical method used in this research is structural equation model (SEM) using AMOS program.The results of this study are. First, self-esteem has a positive effect on financial risk tolerance. Second, personality has a positive effect on financial risk tolerance. Third, sensation-seeking positively affects financial risk tolerance. Young investors can use this study in making an investment or financial decisions in accordance with the level of its financial risk tolerance. For financial consultants, this research can be used in identifying the determinants of financial risk tolerance level in order to suggest the right investment alternatives for clients.